Surgical skill simulation training to proficiency reduces procedural errors among novice cardiac device implanters: a randomized study - Mascheroni, Jorio; Stockburger, Martin; Patwala, Ashish; Mont, Lluís; Rao, Archana; Retzlaff, Hartwig; Garweg, Christophe; Gallagher, Anthony G; Verbelen, Tom (Europace (London, England), 2024)
Abstract Aims In cardiac device implantation, having both surgical skills and ability to manipulate catheter/lead/wire is crucial. Few cardiologists, however, receive formal surgical training prior to implanting. Skills are mostly acquired directly on-the-job and surgical technique varies across institutions; suboptimal approaches may increase complications. We investigated how novel proficiency-based progression (PBP) simulation training impacts the surgical quality of implantations, compared to traditional simulation (SIM) training. Methods and results In this international prospective study, novice implanters were randomized (blinded) 1:1 to participate in a simulation-based procedure training curriculum, with proficiency demonstration requirements for advancing (PBP approach) or without (SIM). Ultimately, trainees performed the surgical tasks of an implant on a porcine tissue that was video-recorded and then scored by two independent assessors (blinded to group), using previously validated performance metrics. Primary outcomes were the number of procedural Steps Completed, Critical Errors, Errors (non-critical), and All Errors Combined. Thirty novice implanters from 10 countries participated. Baseline experiences were similar between groups. Compared to SIM-trained, the PBP-trained group completed on average 11% more procedural Steps (P < 0.001) and made 61.2% fewer Critical Errors (P < 0.001), 57.1% fewer Errors (P = 0.140), and 60.7% fewer All Errors Combined (P = 0.001); 11/15 (73%) PBP trainees demonstrated the predefined target performance level vs. 3/15 SIM trainees (20%) in the video-recorded performance. Conclusion Proficiency-based progression training produces superior objectively assessed novice operators’ surgical performance in device implantation compared with traditional (simulation) training. Systematic PBP incorporation into formal academic surgical skills training is recommended before in vivo device practice. Future studies will quantify PBP training’s effect on surgery-related device complications. Graphical Abstract Graphical Abstract